Efisiensi dan Produktivitas BPJS Kesehatan Tahun 2014 – 2021 (Metode Data Envelopment Analysis dan Malmquist Index) - Selvia Rustyani; Diah Sofiawati; beti rahmawati (BPJS Kesehatan, 2023)
Badan Penyelenggara Jaminan Sosial Kesehatan (BPJS Kesehatan) is a legal entity formed to administer the National Health Insurance program (named JKN) with the principles of social health insurance. Management of social security funds (named DJS) carries high risks. To measure the sustainability of the JKN program, BPJS Kesehatan is required to perform efficiently and productively. This study aims to measure Badan Penyelenggara Jaminan Sosial Kesehatan (BPJS Kesehatan) 's efficiency and productivity from 2014 to 2021. The calculations in this study are relative, not absolute. This non-parametric quantitative research uses Data Envelopment Analysis (DEA) and Malmquist Productivity Index (MPI) methods. This study uses an intermediation approach with BPJS Operational Expenses (X1) as input variables, then Contribution Income (Y1) and Health Insurance Expenses (Y2) as output variables. The results showed that BPJS Kesehatan had inefficiencies in 2014, 2016, 2017 and 2018. As for 2015, 2019, 2020, and 2021, BPJS Kesehatan has achieved an optimal efficiency value of 100%. The Malmquist Index measurement shows that BPJS Kesehatan has experienced an increase in productivity with a score of > 1, except in the second year (2015 – 2016).